The Influence of Complexity on the Adoption of Tissue Culture Banana Seedlings in Tanzania - Tumaini, Steven; Gwahula , Raphael; Macha, Salvio (IJBLE Scientific Publications Community Inc., 2024)
Tissue culture seedlings have been used to improve production in agriculture. However, tissue culture suffers from low adoption. In this context, adoption studies in Tanzania of these types of seedlings are scarce and in general, do not jointly account for the judgment factors affecting the adoption decision among banana farmers. This study investigates the Influence of Complexity on Adoption. Farm-level data were collected through a questionnaire administered to 350 banana farmers in Kilimanjaro. Binary logistic was used to analyse the data and the results show the easier-to-grow significantly increased adoption. The findings of this study propose that; future information on seedlings technology must demonstrate an advantage over traditional seedlings and the investigation evidence supporting seedlings innovation must be clearly visible. We, therefore, concluded that the innovation adoption process has a social and complex element; it requires adequate extension of Information systems and negotiations with key stakeholders in the whole value chain.